Online Learning Communities for Creative Practice - Quinton, Stephen; English, Annie (ACUADS, 2004)
This research project proposes to model the activities and roles of a visiting Research Fellow and an Artist-in-Residence (AIR) with the intent of applying the key educational features and strategies to the online environment. Where feasible, the aim is replicate the role of a Research Fellow online by enlisting the services of well-known artists to contribute their expertise and creative input to the teaching activities of a University School of Art. The primary purpose is to support and enhance the delivery of quality learning outcomes for the Curtin BA (Art) Online degree. The project presents an opportunity to establish wider contact with audiences that have an interest in interacting with an online AIR site to access or contribute research materials and participate in creative activities.In the online environment students are empowered to learn both autonomously as well as actively explore opportunities to teach one another. This emphasis on independent learning is particularly prevalent when asynchronous discussion groups (bulletin boards) are used as an integral part of the learning experience. Students are given the incentive to explain, share, comment, critique, and develop course materials among themselves in ways rarely seen in a traditional classroom setting. The use of electronic alternatives to face-to-face dialogue often results in high quality discussions as students often refer to course materials and reflect on their answers before responding to the lecturer's questions or to classmates' comments. As a result, students have the opportunity to post well-considered comments without experiencing the immediate demands of in-class discussions.The potential of online learning communities will be examined in terms of fostering independent self-directed learning and to encourage online mentoring. Existing examples of practice in online learning will be considered with a view to devising a suitable model for application to online learning communities engaged in creative practices.Of equal importance, the project represents an example of how Curtin is able to form unique collaborations between divergent areas of interest. In this instance, the partnership combines the expertise of the Faculty of Built Environment (BEAD), the School of Art and Design, and the Learning Support Network (LSN).